Experimental study on hysteretic model for L-shaped concrete-filled steel tubular column subjected to cyclic loading. (November 2019) - Du, Guofeng; Zhang, Juan; Li, Yong; Zhang, Jicheng; Zeng, Lei
Abstract: L-shaped concrete-filled steel tubular (L-CFST) column can improve the space layout and can increase the utilization rate of the indoor space. It is a new type of structural column in civil engineering. At present, the research on seismic performance of L-CFST column is insufficient. In this paper, nine L-shaped concrete-filled steel tubular columns were subjected to cyclic loading to study the seismic performance, such as the hysteretic behavior, bearing capacity and stiffness. In the test, three parameters (slender ratio, axial compression ratio and steel ratio) were considered. Simultaneously, the regression analysis of the test results is carried out to establish the hysteretic model of the L-CFST column, and the authors proposed the calculation formulas on the model curve based on the parameters, i.e. load, displacement and stiffness degradation. The results of the hysteretic model of L-CFST columns are in good agreement with the experimental results, which provides a theoretical basis for the analysis of the non-linear seismic behavior of L-CFST columns. Highlights: The seismic behavior of L-shaped concrete-filled steel tubular (L-CFST) column subjected to cyclic loading such as the hysteretic behavior, bearing capacity and stiffness is investigated, and three parameters (slender ratio, axial compression ratio and steel ratio) of L-CFST column were considered. A three-fold line skeleton curve model based on L-shaped concrete filled steel tubular column is proposed, and the corresponding characteristic point formula is defined by fitting with mathematical method based on different parameters, i.e. load, displacement and stiffness degradation. A hysteretic model of the L-CFST column based on the three-fold line skeleton curve model has been carried out.